PELAKSANAAN PEMBELAJARAN SISTEM BLENDED LEARNING PADA PEMBELAJARAN SEJARAH DI MAN KOTA SOLOK - Nisa Ulaini; Sasmi Nelwati; Syahril Syahril (Journal Cerdas Mahasiswa, 2022)
This research was motivated by the 2019 corona virus (covid 19) which spread in Indonesia in early March very rapidly. This has an impact on education which causes learning to change drastically, learning that was originally carried out in face-to-face classes is moved to online learning. However, its decreasing distribution provides hope for educational institutions to carry out face-to-face learning on a limited basis. This means that educational institutions can carry out a combination of face-to-face learning in the classroom and online learning (Blended Learning). This kind of learning is applied in MAN Solok City. This study aims to answer the questions that the researchers have put into the problem formulation, namely to find out how to plan, implement and evaluate blended learning at MAN Solok City. The method in this study uses a descriptive qualitative research method with data collection techniques through interviews, observation and documentation. From the results of the research in the field, it was found that in the process of implementing the blended learning learning system in history learning, it had been implemented starting by dividing the class into several shifts and for online learning using a platform in the form of E-Learning Madrasas and other platforms. There are several advantages, disadvantages and obstacles in the planning, implementation and assessment of blended learning. The impact of this learning is better than the previous online learning.